The Satisfaction Level of Local Batam City Bus (Bimbar), Indonesia - Ahmad Mawardi Lubis; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
Public transportation has a significant role in urban life. One of the well-known public transportation in Batam City is the